Dynamics of PFC power converters subject to time-delayed feedback control - El Aroudi, Abdelali; Orabi, Mohamed (International journal of circuit theory and applications, 2012)
SUMMARY Power factor correction converters are power electronics circuits used as AC‐DC power supplies. These systems are well known to exhibit nonlinear phenomena such as subharmonic oscillations and chaotic regimes. These undesirable behaviors increase the THD and therefore can jeopardize enormously the system performances. In this paper, time delay feedback control is applied to stabilize a two‐stage power factor correction AC‐DC converter when it exhibits these instabilities under traditional controllers. This control technique introduces many advantages to the most and widely used average current mode control through widening the stability domain of the system. By appropriately selecting the time delay feedback gain and the time delay period, the undesirable subharmonic components are eliminated, whereas the desired ones remain unchanged. A harmonic balance approach is used for studying the dynamics of the system under the new control scheme and to obtain the stabilization domain. Copyright © 2010 John Wiley & Sons, Ltd. Power factor correction converters are power electronics circuits used as AC‐DC power supplies. These systems are well known to exhibit nonlinear phenomena such as subharmonic oscillations and chaotic regimes. These undesirable behaviors increase the total harmonic distortion and therefore can jeopardize enormously the system performances. In this paper, time delay feedback control is applied to stabilize a twostage power factor correction AC‐DC converter when it exhibits these instabilities under traditional controllers. This control technique introduces many advantages to the most and widely used average current mode control through widening the stability domain of the system. By appropriately selecting the time delay feedback gain and the time delay period, the undesirable sub‐harmonic components are eliminated while the desired ones remain unchanged. A harmonic balance approach is used for studying the dynamics of the system under the new control scheme and to obtain the stabilization domain. Copyright © 2010 John Wiley & Sons, Ltd.